2003
DOI: 10.1016/s0896-6273(03)00256-3
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Sensitive Potassium Channel Traffic Regulation by Adenosine and Protein Kinase C

Abstract: ATP-sensitive potassium (K(ATP)) channels activate under metabolic stress to protect neurons and cardiac myocytes. However, excessive channel activation may cause arrhythmia in the heart and silence neurons in the brain. Here, we report that PKC-mediated downregulation of K(ATP) channel number, via dynamin-dependent channel internalization, can act as a brake mechanism to control K(ATP) activation. A dileucine motif in the pore-lining Kir6.2 subunit of K(ATP), but not the site of PKC phosphorylation for channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
128
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 85 publications
10
128
2
1
Order By: Relevance
“…Constructs-The Kir6.2 sequence containing an HA tag and an 11-amino acid linker was used as "WT" Kir6.2 (30) and served as a template to generate the following mutant constructs using QuikChange II Site-directed Mutagenesis kit (Stratagene): Kir6.2⌬26-HA, Kir6.2⌬36-HA, Kir6.2T180A-HA, Kir6.2T224A-HA, Kir6.2T224E-HA, and Kir6.2Y330C-HA. The Kir6.2T180A-HA construct was used as a template to generate Kir6.2A180T-HA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructs-The Kir6.2 sequence containing an HA tag and an 11-amino acid linker was used as "WT" Kir6.2 (30) and served as a template to generate the following mutant constructs using QuikChange II Site-directed Mutagenesis kit (Stratagene): Kir6.2⌬26-HA, Kir6.2⌬36-HA, Kir6.2T180A-HA, Kir6.2T224A-HA, Kir6.2T224E-HA, and Kir6.2Y330C-HA. The Kir6.2T180A-HA construct was used as a template to generate Kir6.2A180T-HA.…”
Section: Methodsmentioning
confidence: 99%
“…Dominant-negative dynamin and scrambled control were synthesized (bioSYNTHESIS) according to the published sequence (30).…”
Section: Methodsmentioning
confidence: 99%
“…Lactate modulates the ATP sensitivity of K ATP channels and would accumulate in the vicinity of LDH, and thus of cardiac K ATP channels, under anaerobic conditions [100]. Other examples include direct channel effects of G protein subunits [101,102], changes in the composition of membrane phospholipids that interact with Kir6.2 to modulate pore function [103,104], activation of the protein kinase systems PKC and PKA with channel effects through phosphorylation/dephosphorylation [105][106][107][108], and pH effects through protonation of channel proteins [109].…”
Section: The K Atp Channel Complex As a Component Of The Cellular Enementioning
confidence: 99%
“…Although there are no data for ␤-cells, studies of cardiac and neuronal cells have demonstrated that activation of PKC 3 down-regulates K ATP channels (22). Given the evidence that PKC enzymes in the ␤-cell are activated by glucose stimulation (23,24) and that activation of PKC augments insulin secretion (23,25,26), it is reasonable to speculate that PKC could down-regulate the number of K ATP channels in ␤-cells, thereby enhancing ␤-cell excitability and insulin secretion.…”
mentioning
confidence: 99%
“…It is therefore not surprising that endocytic mechanisms are often targeted by cellular signals, such as protein kinases, to regulate the density of membrane proteins at the plasma membrane (29,30,33). Hu et al (22) reported that activation of PKC stimulates endocytosis of K ATP channels and that little or no channel internalization occurs in the absence of PKC stimulation. However, a later study demonstrated that K ATP channels can undergo constitutive endocytosis in the absence of PKC stimulation using a tyrosine-based endocytic signal located on the Kir6.2 subunit (17).…”
mentioning
confidence: 99%